2008
DOI: 10.1111/j.1651-2227.2008.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Late postnatal systemic steroids predispose to retinopathy of prematurity in very‐low‐birth‐weight infants: a comparative study

Abstract: Significantly more neonates in the ROP group received late postnatal systemic steroids as compared to controls. We speculate that steroids, by altering insulin growth factor-1 (IGF-1) and vascular endothelial growth factor (VEGF) expression, might contribute to the pathogenesis of ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…Seiberth et al , Karna et al and Hoogerwerf et al demonstrated that duration of AV is a risk factor for (severe) ROP 6 10 11. Treatment with dopamine was a risk factor for (severe) ROP in studies of Mizoguchi et al and Liu et al 12 13 Hoogerwerf et al , Smolking et al and the systematic review of the Cochrane database showed that (late) treatment with postnatal steroids is a risk factor for ROP 6 14 15. Lee, Chen et al , Weintraub et al and Jensen et al demonstrated perinatal infection/inflammation or sepsis to be a risk factor for (severe) ROP 1619.…”
Section: Discussionmentioning
confidence: 99%
“…Seiberth et al , Karna et al and Hoogerwerf et al demonstrated that duration of AV is a risk factor for (severe) ROP 6 10 11. Treatment with dopamine was a risk factor for (severe) ROP in studies of Mizoguchi et al and Liu et al 12 13 Hoogerwerf et al , Smolking et al and the systematic review of the Cochrane database showed that (late) treatment with postnatal steroids is a risk factor for ROP 6 14 15. Lee, Chen et al , Weintraub et al and Jensen et al demonstrated perinatal infection/inflammation or sepsis to be a risk factor for (severe) ROP 1619.…”
Section: Discussionmentioning
confidence: 99%
“…6,35 In addition to glucose status, which has been already discussed above, other factors such as exposure to higher mean airway pressure with prolonged mechanical ventilation, 10,36 inotrope therapy, 10,36,37 and postnatal steroid administration 1,38 as well the presence of a PDA, 39 BPD, 39 sepsis 37 and IVH 10 have been also linked to ROP development. Severity of illness is suspected to have a major role in the development of ROP, and potentially explains some of the significant associated factors.…”
Section: Abnormal Glucose Levels In Elbw Infantsmentioning
confidence: 99%
“…Most recent reports point out the presence of normal cerebral development in only 23.5% of VLBW newborns, confirming global, mental and psychomotor retardation in the remaining group with the lack of systemic steroids application [17]. Contrary to that, other data in the literature also underline that the majority of prematures exposed to Dexamethasone in BPD do not develop cerebral palsy or global developmental disability, nevertheless one cannot exclude other more subtle adverse effects after steroids in further periods of childhood [1,8,29,30,[33][34][35].…”
Section: Discussionmentioning
confidence: 94%
“…This pathology is a biphasic process consisting of an initial phase of blunted vascular growth followed by a second phase of vasoproliferation that may be recognized by ophthalmoscopy 6 to 8 wks after birth [1]. Fundamental initiating process involved in retinal vascular development is angiogenesis which is regulated by growth factors, extracellular matrix components and complex of anti-and pro-inflammatory cytokines, among which IL-6, CRP, IL-17, IL-18, TNFα, TGF-β, BDNF, NT4, PDGF, IGF-I, EGF, FGF, PKC -protein kinase C-and HIF-1 α are recognized as key factors in the development of ROP.…”
Section: Introductionmentioning
confidence: 99%